Reconstructing projectile technology during the Pre-Pottery Neolithic B in the Levant: An integrated approach to large tanged points from Halula. (May 2016) - Borrell, Ferran; Štefanisko, Denis
Abstract: Large tanged points made on bidirectional blades constitute the most characteristic tool type during the Pre-Pottery Neolithic B in the Levant. Studies on projectile typology and on bidirectional technology have revealed important stylistic differences reflecting chronological and geographical patterning, contributing significantly to the understanding of early farming communities in the Near East. However, the reconstruction of the weapons these large tanged points were part of has not received the same attention. This investigation aims to fully characterize stone point production at Halula, a PPNB settlement in the middle Euphrates valley, and reconstruct the type of weapons and delivery mechanisms used. Our study also includes the analysis of various ballistic attributes using a series of recent morpho-metric methods and comparison with ethnographic and experimental data about projectiles of known use. Results indicate that Byblos points might have been used as dart-points propelled with the help of spear-throwers, indicating a shift –from bow to spear-thrower– in projectile technology associated with the appearance and expansion of bidirectional blade technology during the PPNB in the Levant and synchronous with the consolidation of agricultural systems in the region. Highlights: This investigation characterizes stone point production and use at PPNB Halula. Ballistic attributes indicate that Byblos points might have been used as dart-points. Expansion of darts use is synchronous with consolidation of agriculture in the region.